Editorial - Mancebo, Deise; Feijoo, Ana Maria Lopez Calvo de; Soares, Adriana Benevides; Tsallis, Alexandra Cleopatre; Barros, Rita Maria Manso de (Estudos e Pesquisas em Psicologia, 2012)
Ana Maria Lopez Calvo de Feijoo, Adriana Benevides Soares, Alexandra Cleopatre Tsallis, Deise Mancebo, Rita Maria Manso de Barros